Upaya Peningkatan Minat Belajar IPAS Siswa Kelas IV Melalui Media Flashcard Berbasis Kearifan Lokal - Hasan, Wilujeng Dewi Latiifah; Hanif Istiani; Fida Chasanatun (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study aims to explain the application of learning through flashcard learning media based on local wisdom can increase student interest in learning which has a direct effect on student learning outcomes in IPAS class IV material on cultural diversity in Indonesia at SDN 1 Dawuhan, Trenggalek District. Problems that are often encountered in learning activities where the low enthusiasm of students in participating in learning is due to the learning process packaged by teachers is less innovative and varied, so this is the background for researchers to design learning media that can solve these problems. The local wisdom-based flashcard learning media is expected to be able to increase student interest in participating in IPAS learning activities and provide space for students at SDN 1 Dawuhan to be more active, and willing to cooperate with others. The type of research conducted by researchers is the Kemmis & McTaggart model of Classroom Action Research. The stages in this study were carried out in two cycles divided into 4 meetings. The subjects in this study were fourth grade students of SDN 1 SDN 1 Dawuhan, Trenggalek District, totaling 10 students. The increase in student interest in learning is indicated by an increase in student learning outcomes in IPAS learning material on cultural diversity through local wisdom-based flashcard learning media seen from the percentage of learning completeness in cycle I of 60%, while the percentage of learning completeness in cycle II rose to 90%. Keywords: Flashcard; Local Wisdom; Interest in Learning; IPAS.